Plant community stability is associated with a decoupling of prokaryote and fungal soil networks - In 't Zandt, Dina; Kolaříková, Zuzana; Cajthaml, Tomáš; Münzbergová, Zuzana (Nature communications, 2023)
Soil microbial networks play a crucial role in plant community stability. However, we lack knowledge on the network topologies associated with stability and the pathways shaping these networks. In a 13-year mesocosm experiment, we determined links between plant community stability and soil microbial networks. We found that plant communities on soil abandoned from agricultural practices 60 years prior to the experiment promoted destabilising properties and were associated with coupled prokaryote and fungal soil networks. This coupling was mediated by strong interactions of plants and microbiota with soil resource cycling. Conversely, plant communities on natural grassland soil exhibited a high stability, which was associated with decoupled prokaryote and fungal soil networks. This decoupling was mediated by a large variety of past plant community pathways shaping especially fungal networks. We conclude that plant community stability is associated with a decoupling of prokaryote and fungal soil networks and mediated by plant-soil interactions.
Keywords: rostliny; zemědělství; Fungi; Plants; Agriculture; půdní mikrobiologie; houby; půda; Soil Microbiology; prokaryotické buňky; Prokaryotic Cells; Soil